2019
DOI: 10.1186/s12885-019-5490-y
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment albumin/fibrinogen ratio as a promising predictor for the survival of advanced non small-cell lung cancer patients undergoing first-line platinum-based chemotherapy

Abstract: Background This study aimed to identify potential predictive factors for the survival of advanced non small-cell lung cancer (NSCLC) patients undergoing first-line platinum-based chemotherapy. Methods A total of 270 advanced NSCLC patients who underwent first-line platinum-based chemotherapy from June, 2011 to June, 2015 were enrolled. A receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive value of the albumin-to-fibrinogen ratio (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
(46 reference statements)
2
17
0
Order By: Relevance
“…These results were consistent with previous research on CRC [10,27]. Increasing studies have used FAR as an independent prognostic factor in patients with resectable ESCC, hepatocellular carcinoma, and advanced nonsmall cell lung cancer, and high levels of FAR can lead to high risk of recurrence and unfavorable OS [8,28,29]. Unfortunately, FAR was not an independent prognostic predictor for resectable GC in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were consistent with previous research on CRC [10,27]. Increasing studies have used FAR as an independent prognostic factor in patients with resectable ESCC, hepatocellular carcinoma, and advanced nonsmall cell lung cancer, and high levels of FAR can lead to high risk of recurrence and unfavorable OS [8,28,29]. Unfortunately, FAR was not an independent prognostic predictor for resectable GC in our study.…”
Section: Discussionsupporting
confidence: 91%
“…To date, several inflammation-based biomarkers, such as C-reactive protein, albumin, neutrophil-to-lymphocyte ratio (NLR), platelet-tolymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and Glasgow prognostic score (GPS), have been revealed as useful prognostic biomarkers in GC, colorectal cancer (CRC), breast cancer, and lung cancer [5][6][7]. In addition, high levels of fibrinogen-to-albumin ratio (FAR), a novel inflammation-based biomarker, are associated with poor outcomes in various cancers, including esophageal squamous cell carcinoma (ESCC), breast cancer, gallbladder cancer, and soft tissue sarcoma [8,9]. More recently, the fibrinogen-to-prealbumin ratio (FPR) was demonstrated to be an excellent diagnostic and prognostic biomarker for patients with CRC and a tool to identify individuals who can benefit from adjuvant chemotherapy treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…As a marker reflecting coagulation function nutritional and the inflammatory status of patients, several studies have used the fibrinogen-to-albumin ratio (FAR) or albumin-to-fibrinogen ratio (AFR) to evaluate the prognosis of various cancer patients, including those with GC, and have found that increased FAR or decreased AFR levels were associated with poor prognosis in cancer patients (12)(13)(14)(15)(16)(17). Another critical role of FAR or AFR is to assess the effect of the chemotherapy regimen in a particular population to guide the selection of an optimal therapy (18)(19)(20). However, there are currently few reports on the pretreatment FAR being used as a marker to predict progression-free survival (PFS) and overall survival (OS) in patients with GC undergoing first-line chemotherapy.…”
Section: Prognostic Value Of Fibrinogen-to-albumin Ratio In Patients mentioning
confidence: 99%
“…Cisplatin-based chemotherapy is considered as the first-line treatment for NSCLC. 13,14 Despite cisplatin-based chemotherapy is effective, development of drug resistance is a usual incidence during the course of cisplatin treatment. 15,16 It is urgent for us to explore useful approaches to reverse the resistance against cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Nowadays, cisplatin-based chemotherapy is still used as the first-line treatment for NSCLC. 13,14 However, virtually all of the NSCLC cells eventually become resistant to cisplatin because of the long-term use of it. 15,16 Novel approaches are required to overcome the resistance of cisplatin in NSCLC.…”
Section: Introductionmentioning
confidence: 99%